ЯНГИБАЙ ДОСУМОВТЫҢ ИЛИМИЙ МИЙРАСЫ - Кощанов, Б.А.; Абдуллаева, З.М. (ILIM hám JÁMIYET, 2025)
This article talks about Ya. Dosumov’s life and his contribution to the development of science in Karakalpakstan.